Grenada : Second Review Under the Extended Credit Facility, Request For a Waiver of a Performance Criterion, Request for Modification of Performance Criteria and Financing Assurances Review. (IMF Staff Country Reports; Country Report ;, 2015)
EXECUTIVE SUMMARY Extended Credit Facility (ECF) Arrangement. The program was approved on June 26, 2014 and the first review completed on December 12, 2014. Grenada has received SDR 4.04 million (about USD 5.9 million) so far under the arrangement and the equivalent of SDR 2 million (about USD 3 million) will be made available upon Executive Board completion of the second review. Debt restructuring. Grenada has achieved a critical milestone in its debt restructuring, reaching agreement on key restructuring terms with its largest private creditor group. The agreement implies a net present value reduction in the related debt of 54 percent and will reduce public debt by 13 percent of 2017 GDP once fully executed. The restructuring of Grenada's debt with the Export-Import Bank of Taiwan Province of China at end-2014 reduced the stock of public debt by another 2 percent of GDP. The authorities expect to finalize negotiations with remaining creditors by end-2015. Program Performance. Overall program implementation remains solid. All but one quantitative performance criteria for the second review were met with wide margins. Major reforms of the fiscal policy framework to anchor debt sustainability have been completed, albeit with some delay, including new fiscal responsibility legislation and the reform of the bulk of the tax incentive regime to eliminate discretion. The strategy to reform parastatal entities has also been completed and its implementation started. Second Review. Discussions focused on meeting the 2015-16 fiscal targets and the structural reform agenda. Modifications are proposed to the 2015 performance criteria to accommodate one-time costs of structural reforms and to the ceiling on non- concessional borrowing to clarify when a loan is considered contracted. Proposed structural conditionality seeks the transparent and sustainable management of citizenship-by-investment receipts and to bring the chart of accounts in line with international best practice.